ANALISIS PENGARUH KUALITAS LAYANAN, CITRA WISATA, INOVASI TERHADAP MINAT KUNJUNG ULANG DENGAN DAYA TARIK WISATA SEBAGAI VARIABEL INTERVENING (STUDI PADA OBYEK WISATA GRAND PURI MAEROKOCO) - Giffen Aldian Widipurnomo; Suryono Budi Santosa (Faculty of Economics and Business | Universitas Diponegoro, 2019)
The development of tourism industry due to needs and wants of each person to travel. People want spent their free time for fun and relaxation, so it makes the managers of Grand Puri Maerokoco Semarang to develop their tourism site’s ability and quality in order to fulfill consumer’s needs and wants. This study aims to explain the influence of service quality, innovation, and destination image in order to influence revisit intention which tourism attraction are used as intervening variables on to Grand Puri Maerokoco Semarang.Sampling of this research was done by using a non-probability sampling with purposive sampling method, in which the peoples who were make visit minimum in twice. The answer of 137 respondents were analyzed using Statistical Package for Social Science (SPSS) 22 with Multiple Regressional Analysis as analytical tool. The first regression to analyze the effect of service quality, innovation, and destination image on tourism attraction. The second regression to analyzed the effect of tourism attraction on revisit intention.The results shows that service quality has positive and significant impact on tourism attraction. Innovation has positive and significant impact on tourism attraction. Destination image has positive and significant impact on tourism destination and also tourism destination has positive and significant impact on revisit intention.